Managing Supplier Requirements with HSE Accounting (Issues in Social and Environmental Accounting (ISEA), 2011)
As recent disasters in the offshore petroleum and other industries illustrate, managing HSE is particularly relevant for companies operating in high risk industrial sectors. HSE management systems support companies in minimising adverse health effects, injuries and environmental damages as well as in complying with legislation, standards and stakeholder expectations. Key elements are risk assessment and control through implementation of preventive and protective measures, the preparation of emergency situations and investigation of accidents. HSE management systems have also become a common element of supply chain audits and management. To increase transparency in their supply chains and to reduce risks, large companies aim at aligning compliance of suppliers with their health, safety and environment (HSE) goals and policy. This paper shows with the case of Bisma Jaya, an Indonesian mechanical engineering company, how accounting for HSE can support small and medium sized suppliers to meet the requirements of large international customers. This paper proposes a framework for HSE management accounting and examines the use of management accounting to improve the HSE performance of an Indonesian company as a response to customer audit requirements. The company is a supplier of a large oil company and seeks for effective and efficient ways of HSE improvement. The paper unfolds benefits and limitations of narrow efficiency-oriented responses to rating systems and audits and highlights that efficiency considerations in HSE management are only partially useful and require complementing effectiveness considerations on HSE performance.